(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This research aims to identify the level of social confidence among the members of the research sample, as well as to identify the differences in social confidence according to the variables of gender, academic specialization, academic year, and marital status. To achieve these goals, the two researchers prepared a social confidence scale and applied it to a sample of (227) male and female students from the faculties of Medicine and Letters (Sociology Department). The search results were concluded as follows: • The level of social confidence among the research sample was moderate. • ‏ There are statistically significant differences between the mean scores of students on the social confidence scale due to the gender variable, in favor of females. • There are no statistically significant differences between the mean scores of students on the social confidence scale due to the variable of academic specialization. • There are statistically significant differences between the mean scores of students on the social confidence scale due to the variable of the school year, in favor of first-year students • There are statistically significant differences between the average performance of the research sample members on the social confidence scale according to • the variable of marital status, in favor of single students‏.